Improved Wave Function for Heavy-light Mesons in QCD Potential Model Approach and Parameterization of the Cornell Potential - Aziz, Abdul; Roy, Sabyasachi; Deshamukhya, Atri (European Journal of Applied Sciences, 2025)
Wereport improved wave function for mesons in QCD potential model approach using multiplicative method for solution of Schr¨odinger equation for the extreme cases of inter quark separations (r → 0 and r → ∞). Using the wave function we find the range of the scale factor c of the Cornell potential with reference to the mass scale of B and D sectors heavy-flavoured mesons. With our computed range of c, we also explore the critical inter quark separation which should govern the choice of parent-child terms in perturbation method out of the linear and Coulombic terms of the Cornell potential.